Effects of aquatic physiotherapy in hospitalized premature in the Neonatal Intensive Therapy Unit (Research, Society and Development, 2021)
Objective: To investigate the effects of aquatic physical therapy in hospitalized premature infants in the Neonatal Intensive Care Unit. Method: This is a non-randomized clinical trial. The sample consisted of 15 preterm newborns. The personal and clinical data of the preterm newborns were collected from the medical record. They were evaluated on two consecutive days: on the first day, the variables of the study (heart and respiratory rate, peripheral saturation, blood pressure, pain and sleep) were evaluated, soon after the blood puncture for the collection of routine exams, and then, the variables were reassessed. On the second day, the procedures of the first day were repeated, however, after the puncture, aquatic physiotherapy was performed. Results: It was observed that the variables heart rate (p